2019
DOI: 10.1021/acsami.9b20101
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Adhesion of Polylactic Acid on Cellulose Surface: A Molecular Dynamics Study

Abstract: Interfacial bonding and adhesion mechanisms are important in determining the final properties of the polymer composite. Molecular dynamics (MD) simulations have been used to characterize the interfacial structure and adhesion behavior of crystalline cellulose planes in contact with polylactic acid. The structure of the PLA at the interface exhibits a shape that can accommodate the structure of the cellulose surface. The adhesion between the PLA and the cellulose surface is affected by the polarity of the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…In order to predict and improve the overall properties of the nanocomposite, it is necessary to understand the structural and dynamic properties of the nanofiller and matrix in the interfacial region. According to Ren et al, 71 PLA tends to approach cellulose surfaces due to the presence of double‐bonded oxygen atoms in the ‐COO group.…”
Section: Resultsmentioning
confidence: 99%
“…In order to predict and improve the overall properties of the nanocomposite, it is necessary to understand the structural and dynamic properties of the nanofiller and matrix in the interfacial region. According to Ren et al, 71 PLA tends to approach cellulose surfaces due to the presence of double‐bonded oxygen atoms in the ‐COO group.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular dynamics is a class of computer simulation methods for statistical mechanical systems, which is suitable for characterizing the interfacial structure and interaction. [ 71 , 72 ] Considering the adhesion energy equaled to the interacting energy of adhesive and adhered, the adhesion energy can be evaluated by: …”
Section: Common Strategies and Test Simulations For Switchable Adhesionmentioning
confidence: 99%
“…Molecular dynamics is a class of computer simulation methods for statistical mechanical systems, which is suitable for characterizing the interfacial structure and interaction. [ 71,72 ] Considering the adhesion energy equaled to the interacting energy of adhesive and adhered, the adhesion energy can be evaluated by: Efalse(adhesionfalse)badbreak=Efalse(totalfalse)goodbreak−Efalse(adhesivefalse)goodbreak−Efalse(adherendfalse)\begin{equation}{E_{{\rm{(adhesion)}}}}{\rm{ = }}{E_{{\rm{(total)}}}} - {\rm{ }}{E_{{\rm{(adhesive)}}}} - {\rm{ }}{E_{{\rm{(adherend)}}}}\end{equation}…”
Section: Common Strategies and Test Simulations For Switchable Adhesionmentioning
confidence: 99%
“…Various factors should be taken into account to predict the overall effect. Molecular dynamics simulations characterized the interfacial structure and adhesion behaviour of crystalline nanocellulose in contact with polylactic acid [ 78 ]. It was found that adhesion between PLA and the surface of cellulose nanofibers is affected not only by the polarity of the functional groups and hydrogen bonds between CNC and PLA but also the surface roughness.…”
Section: Pla/nanocellulose Compositesmentioning
confidence: 99%